Complete Genome Sequence of Klebsiella pneumoniae Myophage Menlow - Newkirk, Heather N. (Microbiol Resour Announc, 2019)
Klebsiella pneumoniae is an opportunistic pathogen that has become an increasing problem in nosocomial infections. Studying phages that infect K. pneumoniae may lead to improvements in phage therapeutics for treating these infections. Here, the full genome sequence of Menlow, a Vi01-like phage, is introduced and described.